The analysis of osseous material from the early medieval camentary in Wilanów - Tomczyk, Jacek (Studia Ecologiae et Bioethicae, 2005)
Acient materials from Wilanow were excavated nearly 40 years ago. It was researched by professor Wiercinski but the results of this work did not appear (it was published only cranial researching). We decided to finish this project – make inventoring, measure, and compare our results. So, the aim of work is to examinate the structure of Wilanow’s population dated back to the early Middle Ages. The whole series is represented by 75 skulls and 48 sketetons. A lot of skulls are very fragmentary, and the analysis is based on the descriptions only of 49 skulls (21 male, 25 female and 3 children). The skulls form Wilanow are interesting because they are approaching the border of brachycephalic. This population is quite different from that one having lived in Poland and dated from this same age. This problem should be researched in the future.